2017
DOI: 10.1080/13880209.2017.1354386
|View full text |Cite
|
Sign up to set email alerts
|

Diospyros kaki calyx inhibits immediate-type hypersensitivity via the reduction of mast cell activation

Abstract: Context:Diospyros kaki L. (Ebenaceae) fruit is widely distributed in Asia and is known to exert anti-inflammatory and antithrombotic effects.Objective: We evaluated the inhibitory effect of aqueous extract of D. kaki calyx (AEDKC) on mast cell-mediated immediate-type hypersensitivity and underlying mechanism of action.Materials and methods: For in vivo, ovalbumin (OVA)-induced active systemic anaphylaxis (ASA) and immunoglobulin (Ig) E-mediated passive cutaneous anaphylaxis (PCA) models were used. In the ASA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Suppresses the Activation of PI3K on IgE−FceRI Stimulation. PI3K consists of the p85 regulatory subunit and the p110 catalytic subunit, and both are involved in mast cell activation signaling (23). During FceRI-mediated mast cell activation, the adapter protein Gab2 binds to the PI3K p85 regulatory subunit and recruits it to the cell membrane, resulting in activation of p85 by Fyn or Syk (5).…”
Section: Rkip Competes With Gab2 To Interact With the Pi3k P85 Subunimentioning
confidence: 99%
See 1 more Smart Citation
“…Suppresses the Activation of PI3K on IgE−FceRI Stimulation. PI3K consists of the p85 regulatory subunit and the p110 catalytic subunit, and both are involved in mast cell activation signaling (23). During FceRI-mediated mast cell activation, the adapter protein Gab2 binds to the PI3K p85 regulatory subunit and recruits it to the cell membrane, resulting in activation of p85 by Fyn or Syk (5).…”
Section: Rkip Competes With Gab2 To Interact With the Pi3k P85 Subunimentioning
confidence: 99%
“…All PI3K p85 isoforms have an N-terminal Src homology 3 (SH3) domain; two Prorich regions near the N terminus; a BCR homology domain, which binds to phosphorylated tyrosine; and a PI3K p110 binding domain located between two Src homology 2 domains, which form the PI3K p85 core domain (SI Appendix, Fig. S5C) (23). Domain-mapping experiments showed that RKIP interacted with p85 in a manner dependent on the domain of the p85 core (aa 332 to 724) but not on the SH3 domain and P-BH-P domain (aa 1 to 331) (SI Appendix, Fig.…”
Section: Rkip Competes With Gab2 To Interact With the Pi3k P85 Subunimentioning
confidence: 99%
“…Reports have shown that the plant has anti-allergic and attenuation effects in atopic dermatitis-like skin lesions. The D. kaki plant extract effectively inhibits the mast cell activation by reducing the expression of a chemokine and proinflammatory cytokines through the modulation of NF-κB signaling pathway (Kim et al 2017;Yu et al 2017). In our previous studies, we demonstrated the anti-inflammatory and anti-melanogenesis effects of quercetin (QC) and its modified form quercetin 3-O-β-D-(2"-O-galloyl)-glucopyranoside (Q32G) isolated from D. kaki (Jung et al 2015;Cho et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the anthelmintic activity, (Sadun & Vajrasthira, 1954) factor-κB. The results suggested that the extract might be a potential candidate for the management of mast cell-mediated allergic conditions (Kim, Park, et al, 2017).…”
Section: Ayoramentioning
confidence: 95%